Psoriatic spondyloarthritis and Sjögren syndrome: a casual association? - V. Bruzzese; C. Marrese; P. Scolieri; J. Pepe (PAGEPress Publications, 2020)
The association between Sjögren syndrome (SS) and psoriatic arthritis (PsA) is rare. Herein, we report a case of SS in a PsA patient with the mutilans variant. A 67-year old woman developed PsA with progressive articular destruction up to the typical deformation of 'telescoping fingers' in the distal phalanges. Psoriatic onychopathy presented ten years after the osteolytic damage in the hands. This late appearance led to delayed diagnosis and therapy, and, consequently, worsened the articular destruction. Thereafter, the patient developed a typical SS with clinical symptoms, such as xerophthalmia and xerostomia. This diagnosis was confirmed by positive diagnostic tests, such as Schirmer test, ANA, and anti-SSA/Ro and anti-SSB/La antibodies. A potential association between the two diseases is discussed.